Toxicité Pour L’abeille Apis Mellifera Adansonii De Trois Herbicides Utilisés En Agriculture Au Bénin - Zoclanclounon, Déo-Gracias; Paraïso, Armand; Paraïso, Grégoire; Akogbéto, Franck; Quenum, Gwladys; Sanni, Ambaliou (European Scientific Journal, ESJ, 2017)
Obtaining high outputs in agriculture requires the use of pesticides to control pests. However, protection of pollinators, precisely bees is very important. The objective of this study was to study the impact on the bee Apis mellifera adansonii of three herbicides usually used in the crop protection in Benin. Ten doses of each herbicide were used and varied from 0.0036.103 (10 ppm) to 1.8.103 nanogram (ng) per bee (5000 ppm) for Roundup, 0.0041.103 (10 ppm) to 2.05.103 nanogram (ng) per bee (5000 ppm) for Glycel and from 0.004.103 (10 ppm) to 2.103 nanogram (ng) per bee (5000 ppm) for Alligator. Each treatment included three replications consisting of 25 bees. Before the treatment, bees were anaesthetized with ether. Observations were made at 2 h, 10 h, 18h, 24h, 36 h and 48 h after the test. Results have shown that 48 hours after, the doses higher or equal to 0.36.103 ng/ab (1000 ppm) of Roundup induced mortality rate higher than 85 %. After 24 hours, the highest mortality rate of Glycel (45.2 ± 1.6 %) was induced by the dose of 1.23.103 ng/ab (3000 ppm). The dose of Alligator of 2.103 ng/ab (5000 ppm) caused the rates respective of mortality of 65.5 ± 2.4 % and 85 % at 24 h and 48 hours after the test. It is necessary to promote sustainable plant protection practices in relation with the use of herbicides to avoid negative impact on bees’ population.